2017
DOI: 10.15403/jgld.2014.1121.262.itl
|View full text |Cite
|
Sign up to set email alerts
|

Eradication Rates in Italian Subjects Heterogeneously Managed for Helicobacter pylori Infection. Time to Abandon Empiric Treatments in Southern Europe

Abstract: Background & Aims: H. pylori eradication is strongly affected by various factors, including the ongoing antibiotic resistance. We describe a “real life” scenario in patients managed for H. pylori-related conditions, living in a southern Italian region (Apulia), an area with clarithromycin resistance >15%.Methods: 2,224 subjects were studied in two tertiary referral centers in Apulia. Analyses included: reason for referral, H. pylori infection rates (13C-urea breath test – UBT or upper endoscopy), and er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 45 publications
2
30
0
1
Order By: Relevance
“…We found that TEAEs occurred in about 16% of treated people, and that in only a minority of cases they caused discontinuation of treatment. This TEAE rate was significantly lower than the others reported by the literature, considering both pivotal studies [13, 14] as well as real life ones [16, 19], except for the study of Di Ciaula et al [18]. In our experience, this anti- H. pylori regimen shows a TEAE rate similar to that of standard triple therapy [3].…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…We found that TEAEs occurred in about 16% of treated people, and that in only a minority of cases they caused discontinuation of treatment. This TEAE rate was significantly lower than the others reported by the literature, considering both pivotal studies [13, 14] as well as real life ones [16, 19], except for the study of Di Ciaula et al [18]. In our experience, this anti- H. pylori regimen shows a TEAE rate similar to that of standard triple therapy [3].…”
Section: Discussionmentioning
confidence: 42%
“…However, our study differs significantly from those experiences. In particular, Di Ciaula et al [18] enrolled both symptomatic and asymptomatic subjects, while the study by Gómez Rodríguez et al [19] was small, enrolling less than 60 subjects. Therefore, our large study population reached more real results, similar to those reached by pivotal studies [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we administered the therapy for 10 days, and a longer 14‐day regimen should be tested. However, high eradication rates were achieved in using the same 10‐day regimen in three recent Italian studies, and in multicenter, European study …”
Section: Discussionmentioning
confidence: 96%
“…However, in the last decade, an eradication rate of >90% has repeatedly been found in all multicenter Italian trials involving thousands of patients [35,36], apart from one study published in 2010 where the infection was cured in 83% of 122 patients [37]. When considering only data from studies published in the last 5 years, the cure rate following sequential therapy was still 90-92.6% in 5 Italian studies with more than 1000 patients [26,38-41], and 73% in another study with 100 cases [42]. A similarly high success rate of sequential therapy has been observed in studies recently performed in Slovenia (94.2%) [43], Portugal (90%) [44], Belgium (90%) [3], Israel (95.9%) [45], Thailand (94%) [46], Taiwan (91.9%) [47], Singapore (90.3%) [48], and the United Arab Emirates (88.6%) [49], suggesting that this therapy is still effective in several countries.…”
Section: Bismuth-free Therapiesmentioning
confidence: 99%
“…The bismuth-based quadruple therapy is included among the recommended first-line therapies in the current European, US, Canadian and Chinese guidelines [8,9,15,19]. Surprisingly, such a therapy was also suggested as an alternative first-line therapy in the Italian guidelines published in 2015, which was before the marketing of these tablets (2016 in Italy) and without any data from Italian trials, the first studies only now being available [41,63]. …”
Section: Bismuth-based Quadruple Therapiesmentioning
confidence: 99%